A marriage of inconvenience: comparing the implementation of the Kenyan and Zimbabwean power sharing agreements - Beardsworth, Nicole Anne (My University, 2012)
The past two decades have seen the rise of power sharing agreements as a means to end protracted civil wars. Following from the perceived success of these agreements, power sharing has become an important tool in the mediator’s arsenal and has increasingly been advocated in periods of democratic deadlock and civil strife following highly-contested elections. The viability of this model has rarely been questioned. This study will undertake a deep analysis of the success or failure of the power sharing agreements undertaken in Kenya and Zimbabwe in 2008 following the outbreak of violence in both countries. It will explain the different results seen in these two cases through an examination of the agreements, the roles played by regional and international actors as well as through an analysis of the influence of local political culture and inter-elite relations. The relative success of the Kenyan agreement can be attributed to a culture of cooperation amongst the elite alongside consistent and concerted pressure exerted by the mediation team and international actors. In contrast, the Zimbabwean government of national unity has hobbled along and little progress has been made to implement the agreement. This can largely be attributed to a badly drafted document which allowed for an inequitable distribution of power, the obduracy of the ZANU-PF elite and the unwillingness of the agreement guarantors to place sufficient pressure on the parties for reform. In a context where inter-elite relations are characterised by opposition and intransigence, the framing of the document and the actions of enforcer parties become particularly important. Due to the political cultures in both countries, it is unlikely that the power sharing agreements will have produced significant gains for democracy or have reformed the prevailing culture of impunity. This report concludes that in spite of the problems with the power sharing model, there are currently few alternatives to help mend torn societies. In order to overcome the problems that have been highlighted within this report, it is necessary for mediators to undertake innovative and reflexive strategies to ensure the full implementation of future agreements.
M.A. University of the Witwatersrand, Faculty of Humanities, 2012
Keywords: democracy; elections; power sharing agreements; electoral violence; Kenya; Zimbabwe